Cleidocranial dysplasia: a case report - P Ghalyani; N Sarrafan (Isfahan University of Medical Sciences, 2009)
Introdution: Cleido cranial Dysplasia (CCD) is a rare autosomal dominant disorder affecting skull and clavicle and may be accompanied by some other skeletal abnormalities. Additionally, delayed tooth development associated with presence of supernumerary teeth has been reported. It is an uncommon disorder with the prevalence being 0.5% per 100'000 live births.Case report: The patient was a 19-year old boy referred to the Department of Oral Medicine of Isfahan Dental College. His chief complaint was an unknown pain in the left side of Maxilla. His intraoral examination revealed presence of deciduous teeth and crowding, missing in permanent teeth. Upon general examination, it was found that he had an abnormal clavicle with hypertelorism and patent anterior fontanel. Panoramic radiography revealed multiple completely impacted supernumerary teeth.Conclusion: Clediocranial dyplasia is a rare skeletal disorder. However, its clinical and radiological manifestations are characteristic. Although this disorder is benign, it must be remembered that abnormal dentition may result in dental caries. For eruption of impacted teeth, especially in young patients, surgical exposure is preferred. Orthodontic occlusal movement must be done for restoring the compatible with normal dental. Keywords: Cliedocranial dysplasia, impacted teeth, multiple supernumerary teeth.